3D morphometry of valley networks on Mars from HRSC/MEX DEMs: Implications for climatic evolution through time. Issue 9 (20th September 2013) - Ansan, V.; Mangold, N.
Abstract: [1] Martian valley networks have been identified mainly in the Noachian heavily cratered uplands. Eight dense branching valley networks were studied in Noachian terrains of Huygens, Newcomb and Kepler craters, south Tyrrhena Terra, and Thaumasia, in Hesperian terrains of Echus Plateau and west Eberswalde craters, and in Amazonian terrains of Alba Patera, using images and digital elevation models from the Mars Express High Resolution Stereo Camera to determine 2D and 3D morphometric parameters. Extracted geomorphic parameters show similar geometry to terrestrial valleys: drainage densities, organization from bifurcation ratios and lengths ratios, Hack exponent consistent with terrestrial values of 0.6, and progressive deepening of valleys with increasing Strahler order. In addition, statistics on valley depths indicate a deeper incision of Noachian valleys compared to younger post‐Noachian valleys (<25 m for Amazonian ones compared to >100 m for Noachian ones), showing a strong difference in fluvial erosion. These characteristics show that dense Martian valley networks formed by overland flows in relation to a global atmospheric water cycle in Noachian epoch and confirm that the later stages of activity may be related to shorter duration of activity, distinct climatic conditions, and/or regional processes, or conditions. Key Points: Dense valley networks have 2D and 3D geometry similar to terrestrial ones Hack exponent on 13 basins show values consistent with terrestrial databases Late Noachian valleys are deeper and more developed than post‐Noachian valleys